ENVIRONMENTAL CARE: THE STRENGTHENING CHARACTER EDUCATION THROUGH ISLAMIC RELIGIOUS EDUCATION (IRE) DEVELOPMENT - Ruslan; Mudjia Rahardjo; Agus Maimun; Rahinah Ibrahim (Balai Penelitian dan Pengembangan Agama Jakarta, 2024)
Dogmatic Islamic Religious Education (IRE) learning in schools seems to lack of attention to environmental issues. Thus, IRE needs to incorporate environment issues. This study aims to analyze the concept and implementation of strengthening environmental care character education through IRE development as well as its implications in framework of eco-culture formation, using MTsN 1 Sumenep and SMPN 2 Larangan Pamekasan as case studies. Using a qualitative approach with a multi-site study design, This research used interviews, observations, and documentation in collected data. The research findings show that the concept of strengthening environmental care character education through IRE development describes efforts to strengthen environmental care character holistically-integrated through curricular, co-curricular, and self-development activities. While its implementation is carried out through 4 stages, namely design which includes identifying the types of activities, developing environment-based IRE study materials, preparing supporting facilities; implementation which includes integrated IRE learning, school management, and student development activities; monitoring and evaluation is carried out through supervision activities and monthly meetings; follow-up refers to school self-evaluation. While the implications can be seen from 3 aspects; the improvement of educational services, changes in learner behavior, a decrease in school operational costs and the existence of class funds.